NAD1 RFLP-PCR FOR DETECTING ECHINOCOCCUS PREVALENCE IN CARNIVORES IN WHITE NILE AREA, SUDAN. A PILOT STUDY (Journal of Veterinary Medicine and Animal Production, 2022)
One hundred fifty eight faecal samples were examined: 150 from stray dogs, 5 from foxes (Vulpes pallida) and 3 from Wild dogs (Lycaon pictus) in different localities within the White Nile Province in Sudan in the period between April 2009 and September 2010 for eggs of Echinococcusspecies. The origin of the faeces was tentatively determined by shape, colour, odour and the presence of field signs. Taeniid eggs were demonstrated in 73 dogs, 3 foxes and 1 wild dog. DNA was isolated from 311 eggs (292 form dogs, 15 from foxes and 4 form wild dogs) for species identification. A previously described restriction fragment length polymorphism (RFLP) - PCR of the mitochondrial nad1 gene was used for species identification. Amplification products were obtained from 51 of the 73 (69.8%).taeniid egg-positive samples obtained from stray dogs, 1/3 (33%) of foxes and none (0%) of wild dogs. E.canadensis (G6) was identified in 100% of those samples. This result was further confirmed by mitochondrial DNA sequencing of a subset of 5 samples of dog and one sample of fox.It was concluded that E. canadensis (G6) appear to be the predominant strain in carnivores in that areas. Further studies including more number of carnivores are highly recommended.